Moderate global nutrient restriction during late gestation did not impact wether lamb development, growth, and performance from weaning to harvest; evaluation of assessment strategy on student retention of knowledge in sequential animal science courses - Kuderka, Alison, author; Cadaret, Caitlin N., advisor; Archibeque, Shawn L., advisor; Bennett, Jennifer, committee member (Colorado State University. Libraries, 2025)
During gestation, pregnant ewes are often managed extensively on rangeland that is not sufficient to meet the nutritional needs of the dam and the fetus, causing nutrient restriction. The performance of these offspring in the pre-weaning period has been well studied; however, there is a lack of studies investigating the effects of maternal nutrient restriction on feedlot and carcass performance of wether lambs after weaning. Thus, the objective of the first study was to investigate the post-weaning performance of lambs from ewes restricted from 110 days of gestation (dGA) to parturition at 65% of NRC requirements. Lambs from restricted dams did not differ in bodyweight or growth rate at any point from lambs born from fully nourished dams. Likewise, lambs from restricted dams did not show evidence of altered nutrient utilization during the balance trial, nor did they have any carcass differences from their control counterparts at harvest. This data demonstrates that nutrient restriction at a moderate level when following full nourishment through early and mid-gestation can be overcome without deficit when also born into a nutrient rich environment. While formative assessment is acknowledged as a meaningful teaching strategy to improve student learning and experience, there is a lack of evidence and implementation of it in undergraduate education. Thus, the objective of the second study was to evaluate student information retention coming from a prerequisite course divergent in assessment strategy and/or environment. The prerequisite course, ANEQ 328: Foundations of Animal Genetics, was delivered in person or online and implemented either exam or quiz-based assessments. At the end of each semester, all students received the same post-test. Furthermore, in the quiz-based courses, students were surveyed at the end of the semester to gather perceptions of learning. In the subsequent course, ANEQ 330: Principles of Animal Breeding, the same post-test from ANEQ 328 was given as a pre-test. Student final grade was greater (P < 0.05) in the quiz-based classroom and in the online classroom. Students in the exam-based classroom performed better (P < 0.05) on the post-test in the prerequisite course. There were no differences in pre-test score or retention across the courses. Student perceptions indicated a preference for formative assessment over summative assessment, yet regardless of classroom type, students felt they could keep up with the material and were well prepared for the subsequent course. These data indicate that both assessment strategies are effective when considering impacts on long-term retention; however, survey data showed that formative assessments are better received than summative assessments, as they help to ease testing anxiety, better pace student learning, and provide consistent feedback. Therefore, instructors may choose to use formative assessments to improve student perceptions of learning without impacting knowledge retention.